Analisis Perlindungan Hukum terhadap Pekerja Kontrak pada Perusahaan Swasta di Indonesia Pasca UU Cipta Kerja - Nikmah Dalimunthe; Wahdaniah Sitorus; Nurliman Prasetyo; Muhammad Rafli Batu Bara; Syifatul Zuhra; Tasya Kusuma Wardani (Journal of Innovative and Creativity, 2025)
This study aims to analyze the legal protection provided to contract workers in private companies in Indonesia following the enactment of the Job Creation Law and its implementing regulations. The research examines key issues including employment status certainty, fulfillment of normative rights, and the effectiveness of the regulatory framework in reducing vulnerabilities faced by contract workers. This study employs a normative juridical method using statutory and conceptual approaches by analyzing primary and secondary legal materials. The findings indicate that although the Job Creation Law offers clearer regulations regarding fixed-term employment agreements, its implementation remains suboptimal due to weak labor supervision and workers’ limited understanding of their rights. Furthermore, several companies continue to apply contract arrangements that are inconsistent with the nature of the job, leading to uncertainty and potential exploitation. Strengthening legal protection for contract workers therefore requires improved law enforcement, increased corporate compliance, and enhanced labor rights education for workers.